Genotype – environment interaction study in sugar beet (Beta vulgaris L.) - Al Jbawi, Entessar; Al Raei, Ahmad Fahd; Al Ali, Ahmad; Al Zubi, Hussain (International Journal of Environment, 2016)
The research was carried out to study the response of 16 cultivars of sugar beet in 3 seasons at one major sugar beet producing location, Hama, in Syria in autumn time, and assess genotype by environment interaction, and to estimate the stability of the varieties performance, according to the yield stability statistics (Ysi), for the studied traits of these varieties. A randomized complete block design with four replications was used. Data collected from each experiment were subjected to simple analysis of variance and after homogenization of error variance, combined analysis for four traits including Sucrose content (SC %), Purity (P %), Root yield (RY ton.ha-1), and Sugar yield (SY ton.ha-1) were carried out. Combined analysis of variance over years, exhibited significant differences (P≤0.05) among the varieties. Results of yield stability statistics (Ysi) revealed that five of the monogerm sugar beet varieties (Vico, Dita, Al Ceste, Chimene, and SR305) were stable for all of the studied traits, during three seasons, which is recommended to be planted in autumn time. International Journal of Environment Vol.5(3) 2016, pp.74-86